A Lexicon Of Basic Vocabulary In The Holy Quran: The “Hamza” Character As A Model/ معجم المفردات الأساسية في القرآن الكريم: حرف الهمزة أنموذجا - Mujahid Mustafa Bahjat; El Sayed Mohamed Salem; Afaf Abdul Ghafoor Hameed (Ijaz Arabi Journal of Arabic Learning, 2023)
The significance of this research is in gathering this vocabulary and its many derived terms to comprehend and assimilate the main Arabic literatur. It also entails defining their meanings to aid understanding and contemplation.Through the eras, these dictionaries about the Qur'an and its terms gradually appeared with various titles and types, and some gained fame in both the past and the present. Writing and research in this area are still ongoing today. This study is a part of a series that alphabetically arranges the most frequently mentioned words in the Qur'an, which we used to refer to as "basic vocabulary," along with their meanings, the number of times they occur in the Qur'an's most derivations, and their first appearance in Surat Al-Baqarah. The research used a descriptive approach to provide the vocabulary and a statistical approach to determine how often it was used. The study presented the "hamza" letter as an example of what the lexicon might look like in the future. It is estimated that this vocabulary and its derivations make up nearly half of the Qur'anic vocabulary.  The research plan was presented as follows: an introduction with the objectives, problem, questions, and limitations of the research; terminology; methodology; and previous studies; a definition of the lexicon and mechanism; a list of vocabulary types; a model of the letter "Hamza"; and a conclusion with sources and references.